1995
DOI: 10.1523/jneurosci.15-11-07539.1995
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of BDNF and trkB mRNA in rat brain by chronic electroconvulsive seizure and antidepressant drug treatments

Abstract: The influence of chronic electroconvulsive seizure (ECS) or antidepressant drug treatments on expression of brain-derived neurotrophic factor (BDNF) and its receptor, trkB, was examined by in situ hybridization and Northern blot. In frontal cortex, acute ECS increased BDNF mRNA approximately twofold, an effect significantly augmented by a prior course of chronic ECS treatment (10 d). In the hippocampus, the influence of chronic ECS varied between the major subfields. In the dentate gyrus granule cell layer, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

75
1,277
11
21

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,904 publications
(1,399 citation statements)
references
References 32 publications
75
1,277
11
21
Order By: Relevance
“…There is also growing evidence that antidepressant treatments may exert some of their therapeutic effects by increasing BDNF expression levels and affecting BDNF transcription in the hippocampus. Thus, (i) electroconvulsive brain stimulation, a treatment of choice for medication‐resistant depression, increases the hippocampal contents of BDNF and trkB mRNAs (Altar, Whitehead, Chen, Wörtwein, & Madsen, 2003; Angelucci, Aloe, JimĂ©nez‐Vasquez, & MathĂ©, 2002; Nibuya et al., 1995), particularly in the dorsal hippocampus (Ploski et al., 2006), (ii) antidepressant treatment rapidly elevates the content of BDNF mature protein via posttranscriptional mechanisms, prevents the stress‐induced decrease in the hippocampal concentration of BDNF mRNA and counteracts the depression‐associated alterations in neural plasticity by normalizing BDNF in the rodent prefrontal cortex and hippocampus (Baj et al., 2012; Kozisek et al., 2008; Musazzi et al., 2009). In keeping with these experimental findings, postmortem samples from clinically depressed patients treated with antidepressant medications show increased BDNF immunoreactivity in the hilus, the dentate gyrus and the supragranular regions of the hippocampus as compared with antidepressant‐untreated controls (Chen, Dowlatshahi, MacQueen, Wang, & Young, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also growing evidence that antidepressant treatments may exert some of their therapeutic effects by increasing BDNF expression levels and affecting BDNF transcription in the hippocampus. Thus, (i) electroconvulsive brain stimulation, a treatment of choice for medication‐resistant depression, increases the hippocampal contents of BDNF and trkB mRNAs (Altar, Whitehead, Chen, Wörtwein, & Madsen, 2003; Angelucci, Aloe, JimĂ©nez‐Vasquez, & MathĂ©, 2002; Nibuya et al., 1995), particularly in the dorsal hippocampus (Ploski et al., 2006), (ii) antidepressant treatment rapidly elevates the content of BDNF mature protein via posttranscriptional mechanisms, prevents the stress‐induced decrease in the hippocampal concentration of BDNF mRNA and counteracts the depression‐associated alterations in neural plasticity by normalizing BDNF in the rodent prefrontal cortex and hippocampus (Baj et al., 2012; Kozisek et al., 2008; Musazzi et al., 2009). In keeping with these experimental findings, postmortem samples from clinically depressed patients treated with antidepressant medications show increased BDNF immunoreactivity in the hilus, the dentate gyrus and the supragranular regions of the hippocampus as compared with antidepressant‐untreated controls (Chen, Dowlatshahi, MacQueen, Wang, & Young, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that, in rats, the bilateral infusion of BDNF into the dentate gyrus of the dorsal hippocampus produces antidepressant‐like effects in behavioral depression models (Shirayama, Chen, Nakagawa, Russell, & Duman, 2002); moreover, in the dorsal hippocampus, chronic electroconvulsive treatment increases the acute electroconvulsive induction and prolongs the expression of BDNF and trkB mRNA (Nibuya et al., 1995), and also up‐regulates the expression of the gene encoding BDNF in the dentate gyrus granule cell layer (Ploski, Newton, & Duman, 2006). Hence, the present study was designed to characterize the hippocampal distribution of BDNF and its receptor trkB in RHA and RLA rats under baseline conditions, with special focus on the dorsal hippocampus, using Western blot (WB) and immunohistochemistry techniques.…”
Section: Introductionmentioning
confidence: 99%
“…36 In addition, BDNF expression can also be regulated by serotonin. 17,37,38 Finally, BDNF promotes survival of rat embryonic septal cholinergic neurons in vitro and increases the activity of enzymes involved in choline acetyl transferase synthesis and degradation. 28 It should be mentioned, however, that BDNF is not as effective as the related and structurally similar NGF in both protection and recovery of the forebrain cholinergic neurons.…”
Section: Bdnf Gives Trophic Support To a Variety Of Cns Neuronsmentioning
confidence: 98%
“…Chronic administration of antidepressants increases BDNF expression in the hippocampus 17,18 BDNF has antidepressant-like activity in learned helplessness paradigms and the forced swim test 19 Environmental stressors decrease central BDNF mRNA 8 Higher BDNF levels in the frontal cortex, occipital cortex, and hypothalamus of the 'depressed' FSL animals relative to the FRL controls 20 Decreased central BDNF in models of stress-induced depression 17,21,22 Downregulation of the Trk-B signaling pathway in the genetic animal models of depression 23 ECS, used as an ECT model, increases BDNF in the hippocampus, striatum, and occipital cortex 24 Lithium increases the expression of BDNF in the hippocampus and cortex of rats 25 BDNF in schizophrenia and depression F Angelucci et al tissue from schizophrenic subjects and MRI data in vivo suggest ongoing specific neurodegeneration. 43 There is also strong evidence suggesting that nonheritable factors in the pathogenesis of schizophrenia are associated with abnormalities during prenatal development.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Regarding the antidepressant action on these plastic phenomena, a well-established effect is to stimulate the synthesis of neurotrophic factors (Nibuya et al, 1995(Nibuya et al, , 1996Chen et al, 2001) and to promote neurogenesis in the hippocampus (Malberg et al, 2000). On the contrary, the effect of antidepressant treatment on cytoskeletal and synaptic plasticity remains controversial.…”
Section: Introductionmentioning
confidence: 99%